Overview of Soft-Switching DC-DC Converters - Abdul-Hakeem Mohammed Dobi; Mohd Rodhi Sahid; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Application of soft switching in DC-DC converter has achieved a remarkable success in power electronics technology in terms of reduction in switching losses, improve in power density, minimization of electromagnetic interference (EMI) and reduction in the volume of DC-DC converters. Quite a number of soft switching techniques had been reported in the past four decades. This paper aims at providing a review of various soft switching techniques, based on topology, the location of the resonant network, performance characteristics, and principles of operation. In addition, converters area of application, advantages as well as limitations are also highlighted.